Lifespan and Decomposition Effects of 1st and 3 rd Generation Silicon Solar Cell with respect to Environment and Health - Sadaf Faryal; Amjad Ali; Abdul Hameed Memon (Sir Syed University Research Journal of Engineering and Technology)
— Utilization of solar photovoltaic is increasing day by day to reduce dependence on the power grid. Decomposition of 1st and 3rd generation silicon solar cells not only depends upon the plastic and other materials but also the hazardous element mainly used as their character on the bases of which they are categorized as 1st , 2nd and 3rd contemporaries solar cells. These ingredient are mostly carcinogenic and some of them having life span of more than 100 years. After abjection of solar cells, they remain in the soil for many years and cause serious problem to land environment and also responsible for causing carcinogenic disease in human and other living beings. This paper explores decomposition rates of the chemical element mainly used in 1st and 3rd generation solar cells throughout the past years, possible environmental and health effects by the hazardous elements used in them typically silicon (atomic number 14) and focusing on possible suggested solutions or alternatives.